2020
DOI: 10.5021/ad.2020.32.6.496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particulate Matter in a Mouse Model of Oxazolone-Induced Atopic Dermatitis

Abstract: Background Recent epidemiological studies have demonstrated that air pollution is associated with the inflammatory response and may aggravate inflammatory skin diseases such as atopic dermatitis (AD). However, it is unclear whether particulate matter (PM) aggravates AD symptoms. Objective The aim of this study was to investigate whether PM exposure affects the skin barrier dysfunction and aggravates AD symptoms using human keratinocytes (HaCaT) cells and a mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Conversely, the expression of skin barrier markers FLG and LOR decreased. The cytokine secretion pattern after exposure to PM appeared to correspond to the in vivo effects related to PM previously shown 33 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Conversely, the expression of skin barrier markers FLG and LOR decreased. The cytokine secretion pattern after exposure to PM appeared to correspond to the in vivo effects related to PM previously shown 33 .…”
Section: Discussionsupporting
confidence: 71%
“…Triple-cell cultures consisting of various cell types can mimic realistic interactions in human skin and is a more reliable evaluation model than traditional cell monocultures 15 . On our previous study 33 , the effects of air pollutants on atopic dermatitis were evaluated by treating keratinocytes with IL-4, IL-13 and PM. Comparison of mRNA and protein expression levels between the single cell model and triple co-culture model showed that there are significant differences in the expression of inflammatory and skin barrier markers in the triple co-culture model even without IL-4 or IL-13 cytokine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matter (PM) is one of the main components of air pollution and is defined as a mixture of gas containing liquid and/or solid droplets varying in size and composition [ 86 , 88 ]. Particles contained in PM include substances such as metals, minerals, organic toxins, tobacco smoke, pollen, allergens, and smog [ 89 ]. These particles are classified according to their aerodynamic diameter (Dp) in three categories: particles with Dp bellow 10 µm are named “coarse particles” or PM 10 and include components of dust, soil, and dusty emission from industries; particles with Dp between 0.1 and 2.5 µm are called “particle matter” or PM 2.5 and are mainly derived from open fires, automobile exhausts, and power plants [ 90 ]; and particles with Dp bellow 0.1 µm are called “ultrafine particles” or PM 0.1 and mainly consist of emissions of diesel-powered engines [ 86 ].…”
Section: Major Components Of Air Pollution Affecting Skin Appearancementioning
confidence: 99%
“…They can affect the human body via the synthesis of reactive oxygen species (ROS) [ 4 , 5 , 6 , 7 ]. Oxidative stress can cause or aggravate the extrinsic aging of the skin and inflammatory skin disorders [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%